Disperse or die: Colonisation of transient open habitats in production forests is only weakly dispersal-limited in butterflies. (February 2018) - Viljur, Mari-Liis; Teder, Tiit
Abstract: Evaluating ecological processes that assemble local animal communities from available species pools has remained a challenging task. At a time of drastic decline of natural and seminatural grasslands, contemporary production forests provide various novel types of open spaces (clear-cuts, power line corridors, etc.) that are potentially suitable habitats for many grassland species, such as butterflies. On the other hand, grassland butterflies are known to perceive forest as a dispersal barrier, potentially limiting the utility of such alternative habitats. We evaluated the role of dispersal limitation in structuring local butterfly assemblages in conventionally managed forest landscapes in which clear-cutting generates varyingly isolated transient open habitats within the forest matrix. We compared butterfly species richness and composition in clear-cuts at opposite ends of a connectivity gradient: sites completely surrounded by forest (isolated clear-cuts) vs. sites connected to the network of other forest clearings by open corridors (non-isolated clear-cuts). We found only a slight difference in the species richness between isolated and non-isolated clear-cuts, both when all open-habitat species and when the subset of grassland species was compared. The frequencies of individual butterfly species in isolated and non-isolated sites were strongly correlated, regardless of their presumed dispersal ability. Our results indicate that, in large areas of production forests in Northern Europe, the formation of local butterfly assemblages is not significantly limited by dispersal. This study contributes to emerging evidence that open spaces in managed forest landscapes can be regarded as alternative habitat for a substantial share of species traditionally considered to be associated with grasslands.